Cobb-Douglass Utility Function in Optimizing the Internet Pricing Scheme Model - Indrawati Indrawati; Irmeilyana Irmeilyana; Fitri Maya Puspita; Meiza Putri Lestari (Universitas Ahmad Dahlan, 2014)
The greater numbers of internet users the greater challenge will be tackled by ISP to provide good services but gain maximum profit. By analyzing Cobb-Douglass utility function we will obtain optimal pricing scheme. Wu and Banker analyzed modified Cobb-douglass utility function and obtained optimal model of flat fee and two part tariff for homogen consumers meanwhile we focus on getting optimal pricing scheme model by using original Cobb-Douglass utility function. The first step to conduct this research is by formulating Cobb-Douglass utility function then analyzing that function. The results show that we obtain optimal pricing scheme model for homogenous and heterogeneous consumer cases. The two-part tariff pricing scheme yield better optimal solution rather than flat fee and two-part tariff pricing scheme regarding with homogen consumers and heterogen consumers based on willingness to pay. For heterogeneous consumers based on consumption level, the optimal pricing scheme is on two-part tariff pricing scheme.